Investigating Feed Rate Effect on Cutting Force of EN 8 Turning - Magdum, Vikas B.; Naik, Vinayak R. (Asian Review of Mechanical Engineering, 2017)
This paper deals with the measurement of cutting force components generated in turning for different cutting parameters and different tools having various feed rates while machining EN 8 steel. The feed rates of the tool were changed using selected cutting parameters; thus, the cutting force components were measured. The selected cutting variables and the tools in different feed rates were tested practically under workshop conditions. During the tests, the depth of cut and cutting speed were kept constant and each test was conducted with a sharp tool. Finally, the effects of cutting parameters and feed rates on cutting forces were analyzed. A cylindrical EN8 work piece was turned using Carbide tools for three feed rates (0.065. 0.13 and 0.26 mm/rev). For feed rate angle, keeping the cutting speed (384 rpm.) and depth of cut (1 mm) constant. During the experimentation, the forces were measured using a dynamometer. The experimental results show that the thrust force (Ft) is greater than the feed force (Ff) irrespective of the feed rates. The cutting forces were found to increase with the increase in feed rate.